Peningkatan Hasil Belajar Pai Melalui Model Problem Based Learning di Kelas VII UPTD SMPN 3 Kecamatan Bukik Barisan - Azimatul Husna; Syawaluddin Syawaluddin; Deslita Deslita; Nurhasanah Nurhasanah; Nur Arifah; Selvi Yanti (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research is motivated by the low learning outcomes in class VII UPTD SMPN 3 Bukik Barisan District in the ability to read the Qur'an, this study aims to improve learning outcomes in class VII UPTD SMPN 3 Bukik Barisan District through the Problem Based Learning Model. The type of research used is Classroom Action Research (PTK) in 4 cycles, each cycle consists of 4 stages, namely planning, action implementation, observation and reflection. Each cycle consists of one meeting (3 lesson hours). The population in the study was 10 students. The data collection techniques used were observation, tests and interviews. The results of this study showed an increase in student learning outcomes from pre-action, in the initial study 3 students (30%) were complete out of 10 students, cycle I as many as 4 students (40%) were complete out of 10 students present, cycle II as many as 5 students (50%) were complete out of 10 students present, cycle III as many as 7 students (70%) were complete out of 10 students present, cycle IV as many as 10 students (100%). Thus, it can be concluded that the application of the Problem Based Learning Model can improve student learning outcomes in the material of reading the Qur'an in the 2024/2025 academic year.